(untitled) (Research, Society and Development, 2023)
Objectives: to describe the historiography and historicity of military women health professionals from the Military Fire Department of the State of Rio de Janeiro in the experience of reproductive planning. Methodology: Qualitative research with a Heideggerian phenomenological approach. Participants were 21 military women from the health teams that provide pre-hospital care, from the coordination of these teams, from a polyclinic and a dental clinic. Interviews were recorded, faithfully transcribed and read attentively. Results: Most women have children, do not live with a partner and also have an active sex life. All have already used some contraceptive method and the most cited was the contraceptive pill. Most stated that they carry out reproductive planning in reports of the decision to have children and highlighting the moment not to use contraceptive methods to achieve motherhood. On the other hand, unplanned pregnancies were also revealed, generating dissatisfaction in some. Women must be assisted by qualified professionals so that reproductive planning is actually carried out effectively, including men in the process. Conclusion: Reproductive planning should be applied and encouraged by health professionals and discussed in its range of actions, complying with public health policies and the principles of the SUS. Nurses must address sexual and reproductive health as soon as possible, through health education and respect for sexual and reproductive rights.